Relevance of Keynesianism in Nepal: An Empirical Analysis - Gaire, Hom Nath (NRB Economic Review, 2014)
In this paper, the relevance of Keynesian postulates has been examined in the Nepalese context for the period 1975-2012 using annual time series data. The empirical results from the Johansen co-integration tests clearly show that there is long run equilibrium relationship between government expenditure and real GDP, private consumption and gross fixed capital formation. Likewise, Granger Causality test confirms that there is bilateral causal relationship between government expenditure and gross fixed capital formation in Nepal. However, no causal relationship is observed between government expenditure and real GDP and private consumption. Thus, it is confirmed by this study that the Keynesian postulates are relevant for capital formation rather than for increasing real GDP growth and private consumption in Nepal.